ByzRev 07.2025.004: Susanna Valpreda, Sikelia 1: La cultura bizantina della Sicilia orientale.: Castelvetrano: Lithos 2023. - Dalbon, Francesco (The Byzantine Review, 2025)
Susanna Valpreda, Sikelia 1: La cultura bizantina della Sicilia orientale. Castelvetrano: Lithos 2023. 384 pp. – ISBN 979-12-80926-10-4